The potential of agroforestry as an adaptation strategy to mitigate the impacts of climate change: A case study of Kiine Community, Kenya - MUNENE ANNE NYARUAI; JOHN K. MUSINGI; BONIFACE N. WAMBUA (Nusantara Bioscience, 2018)
Nyaruai MA, Musingi JK, Wambua BN. 2018. The potential of agroforestry as an adaptation strategy to mitigate the impacts of climate change: A case study of Kiine Community, Kenya. Nusantara Bioscience 10: 170-177. This study has a purpose of evaluating the agroforestry potent as a conformation policy to the effects of climate change in the location of the study. One hundred farmers were used as study sample in collecting data with stratified sampling technique. To achieve data from individual farmers, both arranged and disarranged questionnaires were used. The study utilized questionnaires and observation timetable to collect data from individual farmers associated with the study objectives. The study found out that more preferable practices in agroforestry were planting the trees and shrubs as windbreakers, riparian forest buffers, silvopasture, and boundary planting while the less preferable practices were forest farming, alley cropping, and woodlots. It also found that the coaching to identify both indigenous and exotic agroforestry tree species is needed. In particular, 94% and 90% of the respondents got a feeling that the coaching on agroforestry practices and incorporation of exotic species is needed very much. The reason is that the feeling felt by respondents could give contribution to shortening the prolonged production time of trees on farm. On the contrary, 90% of the respondents are confident that agroforestry can increase catchment yield in rivers and streams, ameliorate the micro-climate, increase wood production as well as increase livestock health and products. The result showed that agroforestry has a direct link in increasing subsistence of people in the study area. Food (fruits), fodder, fuelwood, medicinal substances, gums, tannins, essential oils, fibers and waxes are the examples of agroforestry products sold by the surrounding farmers. The money will be used to provide second-tier facilities such as paying the tuition for their children or even getting healthcare facilities. The result shows that agroforestry is a method in agricultural production which can decrease the effects of human activities and climate change on the local environment. Agroforestry can increase the endurance of agricultural outturn to contemporary climate variance as well as prolonged climate change by means of the utilization of trees for intensification, diversification and supporting of farming systems.